The experiences of newly qualified nurses in intensive care unit: a qualitative meta-synthesis - Wang, Ligang; Chen, Yuan; Yu, Haiyan; Wu, Linjing; You, Aijun; Zheng, Xutong; Zhang, Yunfei (Frontiers in Medicine, 2024)
Background Clinical rotation practicum provides NQNs with more opportunities to learn their professional knowledge and develop basic nursing skills. ICU is often used as one of the clinical practicum departments for NQNs. Nursing shortages have been particularly felt in ICU. Due to the characteristic fast-paced working environments, high acuity of patient care, and technical complexities of an ICU. The experience of NQNs is highly stressful and challenging in these settings, which hinders their professional development and impacts patient care. Aims The study aimed to systematically review and synthesis the findings of qualitative studies exploring experience of NQNs in ICU rotation, to provide a basis for enhancing the quality of clinical nursing. Methods Nine databases were systematically searched for relevant publications from inception until February 2024. All qualitative studies in English and Chinese that explored the experience of NQNs in ICU rotation were collected. Two independent reviewers selected the studies and used The Joanna Briggs Institute Critical Appraisal Tool to evaluate the quality of the studies. Meta-synthesis was performed to integrate the results. Results A total of 13 studies revealed five descriptive themes and 14 sub-themes: ICU readiness, physical and psychological stress, positive self-perception, developing relationships, and ICU reflections. Conclusion Standardized training in ICU, the working ability of NQNs is exercised and their professional quality is improved. However, it is also adversely affected by various stressors. The appropriate guidance and monitoring should be given by hospital managers, so as to promote the development of NQNs and enhance the quality of clinical nursing. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, CRD42023475257.